Gérard Philips and The Triumph of "Via Media": A Historical Note on the Redaction of "Lumen Gentium" - Laksito, Petrus Canisius Edi (Verbum vitae, 2025)
This article aims to investigate the redaction aspects of the dogmatic constitution of the Vatican Council II on the mystery of the Church Lumen Gentium. It is hoped that this attempt will provide a good understanding of the spirit that worked behind the written text and the theological vision that accompanied its creation. In order to achieve this aim, the author presents the historical aspects of the redaction of the document, focusing his attention on the efforts of the main redactor of the document, Mons. Gérard Philips, to introduce a conciliatory approach, a via media, so that there would be no winners nor losers behind the successful realization of the document’s writing. This article begins with a highlight of the essence of the Council as a peaceful process, as wished by Philips. The story continues with the remark on Philips’ painful attempt to redact a new schema,—as the Council Fathers had rejected the original schema previously prepared by the doctrinal commission—due to the negative judgement by Fr. Sebastiaan Tromp, the secretary of the doctrinal commission, who said that the new proposal was "unworthy" of the Council. Yet, Philips’ painful attempt complete the redaction process of the document in peace was ultimately successful, as the majority of the Council Fathers unanimously accepted the final draft of the document, which was subsequently issued as the key document of the Council.